Assessing Students’ Digital Literacy Skill in Senior High School Yogyakarta - Perdana, Riki; Yani, Riwa; Jumadi, Jumadi; Rosana, Dadan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
This study aimed at investigating students’ digital literacy skill of students Grade X and XI in Senior High School in Yogyakarta. There were three steps of this research. First, we constructed the item format and aspect of digital literacy skill. Second, the administration of this research to 193 students of science class in Yogyakarta which were selected randomly. The last, analysis data of students’ digital literacy skill based on educational level. For the profile of students’ digital we used descriptive and quantitative statistics (frequency and percent). To determine the significant difference of the students’ level we also used independent sample t-test. Result of this study showed that the students’ digital literacy skill of all students was very low level. In addition, there was significant difference of students’ digital literacy skill based on educational level. The conclusion was students’ digital literacy skill in Yogyakarta was very low and there must an effort to force these skills. Recommendation for the future study is to develop a learning model that can enhance students’ digital literacy skill. For the policy makers, learning based on digital literacy skill must be integrated on the curriculum. ICT learning should be thought to students in Indonesia, especially in Yogyakarta.